Literature heritage of kokturks and consciouss with turkic-mythology (Eurasian Journal of Philology Science and Education, 2019)
Every nation has an egocentric system of thinking, a way of perceiving the world. It is a nationalworldview and a world of values that form the basis of a national culture that for thousands of years hasabsorbed the consciousness of generations, the mood of traditions, beliefs and convictions, which is thebasis for the full recognition of the nature of the world and clear communication with the outside world.Depending on the history of the Kazakh people, who do not remember so well, the origin of literaryvalues and folklore works consists of sources of mythological origin. It is important to keep in mind thatfolklore and literature combine speech, and on the other hand, each of them has its own characteristics.However, the significant structure of both was shaped by the goals, ideals, and aesthetic tastes of ourancestors. Mythical and religious world viewers are the main contributors to understanding the fundamentals and fundamentals of human relationships with nature in Kok Turkish literature. These conceptsgive the deepest insight into the miraculous manifestations of celestial bodies, animals, labor, and theeveryday use of the works of the era, which we talk about in our stories and fables. These views are considered as tools of the Turkic world view, complementing the processes of belief, extravagance, artistic,psychological emotions, reproduction and strengthening